2019
DOI: 10.1128/aac.00868-19
|View full text |Cite
|
Sign up to set email alerts
|

Novel 5-Nitrofuran-Activating Reductase in Escherichia coli

Abstract: The global spread of multidrug-resistant enterobacteria warrants new strategies to combat these pathogens. One possible approach is the reconsideration of “old” antimicrobials, which remain effective after decades of use. Synthetic 5-nitrofurans such as furazolidone, nitrofurantoin, and nitrofurazone are such a class of antimicrobial drugs. Recent epidemiological data showed a very low prevalence of resistance to this antimicrobial class among clinical Escherichia coli isolates in various parts of the world, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…To investigate the role of these two enzymes in the DOC-FZ synergy, we examined the interaction between DOC and FZ in the ΔnfsA ΔnfsB E. coli strain lacking both of these enzymes. In agreement with the FZ activation role of NfsA/NfsB, disruption of these two genes led to an increase in the MIC causing 50% growth inhibition by a factor of 8 [12]. Nonetheless, the synergy between DOC and FZ still remained significant in the ΔnfsA ΔnfsB genetic background, with the FICI at 50% growth inhibition as low as 0.3125 (Fig.…”
Section: Doc-fz Synergy Is Largely Independent Of Nfsa/nfsbmediated Fsupporting
confidence: 73%
See 2 more Smart Citations
“…To investigate the role of these two enzymes in the DOC-FZ synergy, we examined the interaction between DOC and FZ in the ΔnfsA ΔnfsB E. coli strain lacking both of these enzymes. In agreement with the FZ activation role of NfsA/NfsB, disruption of these two genes led to an increase in the MIC causing 50% growth inhibition by a factor of 8 [12]. Nonetheless, the synergy between DOC and FZ still remained significant in the ΔnfsA ΔnfsB genetic background, with the FICI at 50% growth inhibition as low as 0.3125 (Fig.…”
Section: Doc-fz Synergy Is Largely Independent Of Nfsa/nfsbmediated Fsupporting
confidence: 73%
“…We recently identified a third FZactivating enzyme in E. coli, AhpF, which contributes to this prodrug activation in the ΔnfsA ΔnfsB genetic background [12]. Nevertheless, FZ was still effective against the ΔnfsA ΔnfsB ΔahpF mutant with the MIC 50% being 10-fold increased over the wild-type parent, suggesting the presence of additional 5-nitrofuran-activating enzymes in this organism and/or activation-independent mechanisms of action [12]. Here we analyzed the DOC-FZ synergy in the triple ΔnfsA ΔnfsB ΔahpF mutant and showed that the FICI value was close to that of the wildtype parent and double mutant (Fig.…”
Section: Doc-fz Synergy Is Largely Independent Of Nfsa/nfsbmediated Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of enzymes catalyzing the oxygen-sensitive nitrofuran reduction has not been revealed until 2019, when we identified a novel nitrofuran-activating enzyme by selecting for furazolidone-resistant mutants in an nfsA nfsB E. coli double knock-out strain. A total of 15 independently isolated mutants resistant to bactericidal concentration of furazolidone contained mutations in the ahpF gene, which encodes a component of the antioxidant alkyl hydroperoxide reductase [9]. Subsequent enzymatic assays of purified AhpF protein determined that this enzyme is a type II oxygen-sensitive nitroreductase [9].…”
Section: Nitrofuran-activating Enzymes In Escherichia Colimentioning
confidence: 99%
“…In this spirit, a possible novel nitrofuran resistance mechanism(s), besides well-known nfsA/nfsB mutations, must receive due attention and resources in order to sustain the utility of this drug class. While the prevalence of nitrofuran resistance among E. coli clinical isolates in recent epidemiology surveys around the world is still low [9], nitrofuran-hyperresistant isolates with the MIC higher than 128 μg/mL have been encountered [15,16]. This high level of resistance cannot solely be explained by mutations in the nfsA, nfsB, and ahpF genes and points to unknown resistance determinants that are already circulating in pathogenic strains.…”
Section: Nitrofuran Resistance Mechanisms In E Colimentioning
confidence: 99%